What Do We Know of Childhood Exposures to Metals (Arsenic, Cadmium, Lead, and Mercury) in Emerging Market Countries? - Lindsey M. Horton; Mary E. Mortensen; Yulia Iossifova; Marlena M. Wald; Paula Burgess (International Journal of Pediatrics)
Arsenic, cadmium, lead, and mercury present potential health risks to children who are exposed through inhalation or ingestion. Emerging Market countries experience rapid industrial development that may coincide with the increased release of these metals into the environment. A literature review was conducted for English language articles from the 21st century on pediatric exposures to arsenic, cadmium, lead, and mercury in the International Monetary Fund's (IMF) top 10 Emerging Market countries: Brazil, China, India, Indonesia, Mexico, Poland, Russia, South Korea, Taiwan, and Turkey. Seventy-six peer-reviewed, published studies on pediatric exposure to metals met the inclusion criteria. The reported concentrations of metals in blood and urine from these studies were generally higher than US reference values, and many studies identified adverse health effects associated with metals exposure. Evidence of exposure to metals in the pediatric population of these Emerging Market countries demonstrates a need for interventions to reduce exposure and efforts to establish country-specific reference values through surveillance or biomonitoring. The findings from review of these 10 countries also suggest the need for country-specific public health policies and clinician education in Emerging Markets.